Implementation of TQM in public universities of Saudi Arabia: challenges and resolutions - Ghassan Alseddiqi, Abdul Rahman (IIUM Press, International Islamic University Malaysia, 2017)
Saudi Arabian universities are keen, as universities in many other nations, to improve quality in tertiary education provided by them. Almost all the public universities have embarked upon implementing Total Quality Management or TQM in their campuses. However, there are many issues and challenges in successful implementation of TQM programs. The present book highlights those challenges. In addition to these, possible solutions are proposed to reap maximum benefits of TQM implementation in academic campuses.